(3gOjI GdQMje GdQMef dCgd GdEjeGf aj aVGFd djdI fUa TYHGfs - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi jYWi ef jTGA hjefY ef jTGA agh GdeYWi GdeGfY CeG HYO GYde Cf GddjdI GdfUa ef TYHGf CSeGA cKjQI hcKQI GdCSeGA JOd Ydi TQa GdeSei s
(3BNQgG (B:s
(3hef CQGO aVGFd eG hQO ajg GdPcQ aYdjg HTQMfG Ydi GdhXjaI GdRQhbjg hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3GdfSNI HgG MhGTs
(3JUhas
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs